Current approaches to diagnosing in intracerebral hemorrhage - A. A. Kulesh (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2020)
Intracerebral hemorrhage (ICH) is the same etiologically heterogeneous variant of stroke as cerebral infarction. The most common causes of the disease are hypertensive and cerebral amyloid microangiopathy, the use of oral anticoagulants (OACs) and their combination, and arteriovenous malformations, which are of the greatest importance for young patients. The SMASH-U or H-ATOMIC classification of ICH requires a structured diagnostic search that includes an analysis of the clinical presentations of the disease and neuroimaging and angiographic findings. Although brain computed tomography remains a basic diagnostic technique for ICH, most patients need brain magnetic resonance imaging, by mandatorily assessing the ischemic and hemorrhagic markers of cerebral small vessel diseases. This examination is necessary not only to verify the cause of ICH and to select the appropriate method of its treatment, but also to determine the risk of recurrent hemorrhage. The article considers the epidemiology and etiological characteristics of ICH and approaches to its classification. It characterizes the most significant causes of the disease, such as hypertensive and cerebral amyloid angiopathy, vessel structural abnormalities, and the use of OACs. Thediagnosis of ICH and its clinical neuroimaging diagnostic algorithm are presented.